Potential for hydroxamic acid modification via electronic effect: A case study of enhanced cassiterite flotation - Zhang, Zhifeng; Yu, Yao; Fu, Junhao; Cao, Jian; Deng, Chaozheng; Sun, Wei; Han, Haisheng (Minerals engineering, 2025)
•Based on the electronic effect, three novel hydroxamic acids were designed and synthesized.•The collecting performance order for cassiterite was: PHA > CHA > AHA > BHA.•The introduction of para-methoxy group and double bond leverages the inductive-conjugative synergy.•PHA exhibits superior chelating coordination ability, leading to stronger adsorption on cassiterite surface. Despite the selectivity highlighting, the improvement of collecting capacity of hydroxamic acids remains a significant challenge. In this study, commencing from the electronic effect and based on the benzohydroxamic acid (BHA) skeleton, three novel hydroxamic acids, anisohydroxamic acid (AHA), cinnamohydroxamic acid (CHA), and p-methoxy cinnamohydroxamic acid (PHA), were designed and synthesized via double-bond extension and the introduction of a para-methoxy group. Taking cassiterite as the research subject, the impact of hydroxamic acids with enhanced electronic effect on the collecting performance was explored. Results of single-mineral flotation tests indicated that, with identical dosages, the cassiterite recovery decreased in the following order: PHA > CHA > AHA > BHA, aligning with the prediction derived from quantum chemical properties. Subsequent investigation revealed that the methoxy group of AHA not only served as an electron-donating moiety, conducting electrons to the functional hydroxamic acid group via the conjugated system of benzene ring, but also significantly enhance the hydrophobic property of the collector, as evidenced by the contact angle tests. Besides, FTIR and XPS analysis suggested that the incorporation of unsaturated bonds within CHA boosted its adsorption intensity at the Sn4+ active sites, benefiting from the extended conjugation effect. AFM imaging confirmed the above conclusions and determined that PHA, featuring both double bond and para-methoxy group, emerged as a preferable collector for cassiterite. In contrast to BHA, PHA, acting as a bidentate ligand, exhibited a more compact adsorption configuration on cassiterite (110) plane, accompanied by a significantly lower adsorption energy. Collectively, the hydroxamic acid modification strategy grounded in electronic effect proved to be highly efficient and viable, offering substantial potential for enhancing the flotation performance of refractory oxidized ores.